Celecoxib accelerates functional recovery after sciatic nerve crush in the rat - Camara Lemarroy, Carlos Rodrigo; Guzmán de la Garza, Francisco Javier; Barrera Oranday, Ernesto; Cabello García, Andrés Jesús; García Tamez, Armando; Fernández Garza, Nancy Esthela (2014)
The inflammatory response appears to be essential in the modulation of the degeneration and regeneration process after peripheral nerve injury. In injured nerves, cyclooxygenase-2 (COX-2) is strongly upregulated around the injury site, possibly playing a role in the regulation of the inflammatory response. In this study we investigated the effect of celecoxib, a COX-2 inhibitor, on functional recovery after sciatic nerve crush in rats. Unilateral sciatic nerve crush injury was performed on 10 male Wistar rats. Animals on the experimental group (n = 5) received celecoxib (10 mg/kg ip) immediately before the crush injury and daily for 7 days after the injury. Control group (n = 5) received normal saline at equal regimen. A sham group (n = 5), where sciatic nerve was exposed but not crushed, was also evaluated. Functional recovery was then assessed by calculating the sciatic functional index (SFI) on days 0,1,7,14 and 21 in all groups, and registering the day of motor and walking onset. In comparison with control group, celecoxib treatment (experimental group) had significant beneficial effects on SFI, with a significantly better score on day 7. Anti-inflammatory drug celecoxib should be considered in the treatment of peripheral nerve injuries, but further studies are needed to explain the mechanism of its neuroprotective effects.